2022
DOI: 10.3390/w14132018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Glacially Derived Runoff in the Muzati River Watershed Based on the PSO-LSTM Model

Abstract: The simulation and prediction of glacially derived runoff are significant for water resource management and sustainable development in water-stressed arid regions. However, the application of a hydrological model in such regions is typically limited by the intricate runoff production mechanism, which is associated with snow and ice melting, and sparse monitoring data over glacierized headwaters. To address these limitations, this study develops a set of mathematical models with a certain physical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In an LSTM cell, there are three gate units: the forget gate, the input gate, and the output gate. The relevant mathematical equations are as follows [35,36], and the network architecture is illustrated in figure 9.…”
Section: Lstm Neural Networkmentioning
confidence: 99%
“…In an LSTM cell, there are three gate units: the forget gate, the input gate, and the output gate. The relevant mathematical equations are as follows [35,36], and the network architecture is illustrated in figure 9.…”
Section: Lstm Neural Networkmentioning
confidence: 99%
“…The principle of the Particle Swarm Optimization algorithm is to find the optimal solution through the collaboration and information sharing between individual particles within the swarm. Particle swarm optimization algorithm has the advantages of small computational cost and fast convergence, so it is very convenient when used for models with strong real-time requirements [26,27].…”
Section: Pso Principlementioning
confidence: 99%
“…The comparison results indicated that the BP model optimized by the PSO algorithm provides better prediction performance. Yang et al [15] used PSO and LSTM model coupling to predict glacier runoff. According to the results, the PSO-LSTM model exhibited better forecasting accuracy than the LSTM model.…”
Section: Introductionmentioning
confidence: 99%